On the reversed crystal growth of BaZrO3 decaoctahedron: shape evolution and mechanism - Moreira, Mario L. [UNESP]; Andres, Juan; Mastelaro, Valmor R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Royal Soc Chemistry, 2011)
BaZrO3 (BZO) nanoparticles were nucleated, grown and subsequently self-assembled into a 3D decaoctahedronal architecture via a microwave-assisted hydrothermal (MAH) method. X-Ray diffraction (XRD), field emission scanning microscopy (FE-SEM), X-ray absorption spectroscopy (XAFS) as well as both photoluminescence (PL) and radioluminescence (RL) emission studies have provided fundamental insight into the nature of the anisotropic crystal growth mechanism of BZO nanocrystals into their final decaoctahedral shape. The growth mechanism of the assembled nanoparticles via mesoscale transformations to form BZO decaoctahedrons occurs from the surface to the core along a reversed crystallization route. This pathway is accompanied by a large enhancement of RL emissions while the intensity of PL emissions is enhanced and worsened along the process. The analysis of the results reveals a relationship between the decaoctahedrons obtained and their optical properties.